2017
DOI: 10.1007/s00261-017-1320-3
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative free-breathing dynamic contrast-enhanced MRI in hepatocellular carcinoma using gadoxetic acid: correlations with Ki67 proliferation status, histological grades, and microvascular density

Abstract: The DCE-MRI derived parameters demonstrated weak but significant correlations with tumor proliferation status, histological grades or microvascular density, respectively. This free-breathing DCE-MRI is technically feasible and offers a potential avenue toward non-invasive evaluation of HCC malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 55 publications
1
23
0
Order By: Relevance
“…Wu et al found that a radiomics analysis based on MRI had the potential to discriminate HCCs with a high ES grade with an AUROC of 0.742 to 0.8. Chen et al found that the MRI perfusion parameter K trans had the best diagnostic sensitivity and specificity for distinguishing HCCs with a high grade (93.3% and 63.2%, respectively), with an AUROC of 0.78. In general, the D value was superior to the ADC value and other MRI techniques in the pathological grading of poorly differentiated HCCs.…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al found that a radiomics analysis based on MRI had the potential to discriminate HCCs with a high ES grade with an AUROC of 0.742 to 0.8. Chen et al found that the MRI perfusion parameter K trans had the best diagnostic sensitivity and specificity for distinguishing HCCs with a high grade (93.3% and 63.2%, respectively), with an AUROC of 0.78. In general, the D value was superior to the ADC value and other MRI techniques in the pathological grading of poorly differentiated HCCs.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study from Chen et al[ 39 ], the max-Ktrans seemed to correlate with tumor grades (rho = -0.382, P = 0.028). The Ktrans, Kep, and iAUC of high-grades HCC were significantly lower than that of low-grades HCC ( P = 0.001, 0.031, 0.003, respectively), but there was no statistically significant differences for Ve between high grade and low grade HCC ( P > 0.05)[ 39 ].…”
Section: Perfusion Imagingmentioning
confidence: 96%
“…Previous studies indicated correlations between K trans and microvessel density in several malignancies [ 7 , 9 ]. Also some authors suggested that K trans correlated with proliferation activity (KI 67 expression) in hepatocellular carcinoma [ 26 ]. However, this did not apply for all lesions [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tumor proliferation index as relation of KI 67 stained nuclei divided by all nuclei [ 25 , 26 ]. Though for the analysis the area with the highest number of positive tumor nuclei was selected (Figure 1 );…”
Section: Methodsmentioning
confidence: 99%